Energieffektivisering i hamburgerrestaurang - Nordström, Jenny (2012)
In this project a tool for visualization of energy use is developed. It is a joint project between Luleå Energi and MAX in order to push development of energy efficient production forward. The work includes basic measuring, development of graphics, equipment selection and installation of visualization equipment at three restaurants, located in Piteå, Vasagatan and Arninge sited in Stockholm. A comparison number has been developed that compare energy use set to turnover. The results show that the energy usage at the restaurant in Piteå has decreased with an average of 8% according to this comparison number during the test period.Experience during the test period indicates that there is a need for visualization and feedback at MAX. This, despite the great interest the employees at the company already have within this area. They are actively working on reducing their climate impact since a few years back. Overall, the staff at the restaurants is positive to this tool as an aid in their efforts to reduce energy use. Validerat; 20121219 (global_studentproject_submitter)